2, 6‐Bis(amido)benzoic Acid with Internal Hydrogen Bond as Brønsted Acid Catalyst for Friedel–Crafts Reaction of Indoles. Issue 9 (15th June 2015) - Moriyama, Katsuhiko; Sugiue, Toru; Saito, Yuki; Katsuta, Shoichi; Togo, Hideo
Abstract Benzoic acid catalysts bearing two amide groups that increase the Brønsted acidity of the carboxylic acid moiety by internal hydrogen‐bonding interactions were designed as a novel class of carboxylic acid catalysts for the Friedel–Crafts reaction of indoles with β‐nitrostyrenes and 3, 3‐disubstituted 3H‐indoles to obtain the corresponding Friedel–Crafts adducts in high yields. The internal hydrogen‐bonding benzoic acid catalysts have a relatively high Brønsted acidity compared with benzoic acid based on the pKa measurements in DMSO by UV spectrophotometric titration.